Subcortical Local Functional Hyperconnectivity in Cannabis Dependence - Manza, Peter; Tomasi, Dardo; Volkow, Nora D. (Biological psychiatry : cognitive neuroscience and neuroimaging, 2018)
Cannabis abuse (CA) has been associated with psychopathology, including negative emotionality and higher risk of psychosis, particularly with early age of initiation. However, the mechanisms underlying this association are poorly understood. Because aberrant dopamine signaling is implicated in cannabis-associated psychopathology, we hypothesized that regular CA would be associated with altered resting-state functional connectivity in dopamine midbrain-striatal circuits. We examined resting-state brain activity of subcortical regions in 441 young adults from the Human Connectome Project, including 30 subjects with CA meeting DSM-IV criteria for dependence and 30 control subjects matched on age, sex, education, body mass index, anxiety, depression, and alcohol and tobacco usage. Across all subjects, local functional connectivity density hubs in subcortical regions were most prominent in ventral striatum, hippocampus, amygdala, dorsal midbrain, and posterior-ventral brainstem. As hypothesized, subjects with CA showed markedly increased local functional connectivity density relative to control subjects, not only in ventral striatum (where nucleus accumbens is located) and midbrain (where substantia nigra and ventral tegmental nuclei are located) but also in brainstem and lateral thalamus. These effects were observed in the absence of significant differences in subcortical volumes and were most pronounced in individuals who began cannabis use earliest in life and who reported high levels of negative emotionality. Together, these findings suggest that chronic CA is associated with changes in resting-state brain function, particularly in dopaminergic nuclei implicated in psychosis but that are also critical for habit formation and reward processing. These results shed light on neurobiological differences that may be relevant to psychopathology associated with cannabis use.